Stiffness identification of magnetic suspension system based on zero-displacement and zero-current models. (15th May 2022) - Xiang, Biao; Li, Zhongbo; Wong, Waion
Graphical abstract: This research results would be applied to stiffness identification of the magnetically suspended rotor system with residual unbalance and vibration. The proposed method has the advantage of no additional component and cost incurred because it just makes use of the displacement sensor and the current sensor which are standard components of the magnetically suspended rotor system. Highlights: Zero-displacement and zero-current models designed for MSFW rotor control. Frequency analyzes of zero-displacement and zero-current models. Stiffness estimation using synchronous components of displacements and currents. Abstract: Based on the dynamic displacement and the control current of the magnetically suspended flywheel (MSFW) system with great self-weight, an identification method of the displacement and current stiffnesses of MSFW rotor is proposed in this article. The structure of MSFW rotor is introduced, and the dynamic displacement models of MSFW rotor in radial directions are established. Furthermore, to obtain the current stiffness and the displacement stiffness, control models including the zero-displacement model and the zero-current model are designed for MSFW rotor, and then the frequency characteristics of the zero-displacement model and the zero-current model are analyzed. Finally, experiments are conducted to measure the synchronous components of dynamic displacements and control currents so that the displacement and current stiffnesses of the MSFW system can be estimated.